Adaptive approaches to REDD+ are needed for countries with high forest cover and low deforestation rates - Melanie Schweikart; Ole Mertz; Daniel Müller (Environmental Research Letters, 2022)
Reducing emissions from deforestation and forest degradation (REDD+) aims to maintain forest carbon stocks above benchmark reference levels through financial compensation. However, countries with high forest cover and low deforestation (HFLD) are unlikely to be compensated fairly if REDD+ initiatives fail to conserve existing forests and to incentivize low deforestation rates. Here we analyze the submissions of forest reference levels (FRLs) of five HFLD countries [Democratic Republic of the Congo (DRC), Republic of the Congo (Congo), Guyana, Papua New Guinea, Suriname] to the REDD+ platform of the United Nations Framework Convention on Climate Change. We assessed if the FRLs are likely to yield compensation payments that maintain carbon stocks above the business-as-usual scenario and compared the FRLs with quantitative emission data. Our results show that only Guyana submitted an FRL that yielded sufficient monetary incentives for low deforestation rates. Compensation payments will likely be insufficient in Suriname, Papua New Guinea, and the Congo. The FRL of the DRC would generate the highest compensation payment (on average US 1.3 billion annually). Overall, our results suggest that payments from REDD+ will fail to provide adequate incentives for most HFLD countries. We suggest that the FRL should allow for post hoc adaptation to changes in the drivers of deforestation. This implies that REDD+ schemes need sufficient flexibility to reflect changes in the opportunity costs of alternative land uses, which is particularly acute for HFLD countries where pressure on forests can accumulate rapidly. More adaptive REDD+ likely better rewards HFLD countries in ways that preserve their valuable forest ecosystems.
Keywords: 330; tropical deforestation; primary forest; greenhouse gas emissions; emission reductions; mitigation; climate policy; land-use change